2015
DOI: 10.1002/cpdd.221
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence and comparative pharmacodynamics of insulin lispro 200 U/mL relative to insulin lispro (Humalog®) 100 U/mL

Abstract: Insulin lispro 200 U/mL (IL200) is a new strength formulation of insulin lispro (Humalog®, IL100), developed as an option for diabetic patients on higher daily mealtime insulin doses. This phase 1, open‐label, 2‐sequence, 4‐period crossover, randomized, 8‐hour euglycemic clamp study aimed to demonstrate the bioequivalence of IL200 and IL100 after subcutaneous administration of 20 U (U) to healthy subjects (n = 38). Pharmacokinetic (PK) and pharmacodynamic (PD) responses were similar in both formulations. All 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 9 publications
0
36
0
4
Order By: Relevance
“…A weighted local regression technique (LOESS) with a smoothing factor (SF) of 0.1 for calculation of time-related parameters and maximum GIR in accordance with previous studies that investigated the pharmacodynamics of short-acting insulin. 23 The pharmacodynamic endpoints calculated for each clamp study visit (Visits 2b, 3 and 4) were maximum glucose infusion rate (GIR max ) and time to maximum glucose infusion rate (t GIRmax ). In addition to total area under the curve (AUC) for GIR from 0-6 h (AUC GIR.0-6h ), partial AUCs from 0-1, 0-2 hours (AUC GIR.0-1h ), 0-6 hours (AUC GIR.0-2h ) and 2-6 hours (AUC GIR.2-6h ) following insulin injection were also calculated to determine early and late insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…A weighted local regression technique (LOESS) with a smoothing factor (SF) of 0.1 for calculation of time-related parameters and maximum GIR in accordance with previous studies that investigated the pharmacodynamics of short-acting insulin. 23 The pharmacodynamic endpoints calculated for each clamp study visit (Visits 2b, 3 and 4) were maximum glucose infusion rate (GIR max ) and time to maximum glucose infusion rate (t GIRmax ). In addition to total area under the curve (AUC) for GIR from 0-6 h (AUC GIR.0-6h ), partial AUCs from 0-1, 0-2 hours (AUC GIR.0-1h ), 0-6 hours (AUC GIR.0-2h ) and 2-6 hours (AUC GIR.2-6h ) following insulin injection were also calculated to determine early and late insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…Clamp studies have demonstrated discordance between rapid-acting insulin analogue PK properties (absorption time) and PD properties (action time), which creates an obstacle in successfully replicating prandial, physiological insulin action (we have not found any clinical data that explain the differences seen between the PK and PD characteristics of these insulin analogues). For example, a study comparing PD profiles of insulin lispro 100 U/ml and insulin lispro 200 U/ml found that, although the times to maximum insulin concentration were 45 and 60 min, respectively, the times to maximum GIR were similar (120 vs 126.6 min for insulin lispro 100 vs 200 U/ml) [28]. Another study highlights the potential difference in timing of important outcomes.…”
Section: What's New?mentioning
confidence: 99%
“…Insulin lispro U100 (ILis100) has been used in a variety of patient populations at varying doses and regimens over a 20-year period, 25,26 and data concerning the ILis100 insulin formulation can be used to inform the use of insulin lispro U200 (ILis200) because they are bioequivalent. 2 In contrast, insulin degludec U200 (IDeg200) is newer to the market. Each concentrated insulin is derived from its U100 counterparts.…”
Section: Myth 1: All Concentrated Insulins Have Similar Safety Effmentioning
confidence: 99%
“…Both ILis200 and IDeg200 are bioequivalent to their U100 counterparts. 1,2 Because ILis200 is bioequivalent to ILis100 (Fig. 3a) it can be used at the same dosage, unit-forunit, and the safety and efficacy are expected to be similar.…”
Section: Myth 1: All Concentrated Insulins Have Similar Safety Effmentioning
confidence: 99%
See 1 more Smart Citation